Development of a System for Determining Loan Eligibility in the Bukit Indah Cooperative, Batunya Village Using the Fuzzy Sugeno Method - Gunawan, I Gede Made Deny Surya; Kertiasih, Ni Ketut; Marti, Ni Wayan; Permana, Agus Aan Jiwa (Lembaga Yasin AlSys, 2024)
This study aims to develop a loan eligibility determination system at the Bukit Indah Cooperative in Batunya Village using the fuzzy sugeno method. The Bukit Indah Cooperative is a savings and business cooperative run independently by the Batunya Village community and carries out efforts for the welfare of the Batunya Village community. Fuzzy Sugeno is one of the fuzzy logic methods used for modeling, control and decision making. Fuzzy Sugeno was developed by Takagi, Sugeno, and Kang in 1985, this method aims to provide more efficient results in the control and decision making system. The research method used in this study is the waterfall method. This study has succeeded in developing and producing a system used to help the Bukit Indah Cooperative in Batunya Village to determine the eligibility of providing loans to customers. In testing the feasibility of the system with 20 sample data, it was found that out of 20 sample data, there were 18 correct data in the system, data comparison was carried out by comparing the data from the evaluation of calculations by cooperative officers with the data produced by the system which produced an accuracy level of 90.00%. Based on these results, it was found that the system developed can be said to work well and is considered sufficient to test the accuracy of the fuzzy Sugeno method.